Theoretical optimization of magnetoelectric multilayer laminates - Martins, Pedro Libânio Abreu (2021)
Magnetoelectric (ME) materials are becoming increasingly relevant in the development of new technologies for biomedical applications, sensors and actuators, among others. Mathematical models and simulations allow to optimize features and acquire fundamental knowledge on material properties to achieve innovative developments and devices. In this way, this work is focused on the simulation of both polymer-based and ceramic-based ME laminates, in order to evaluate the influence of their structure, mechanical, electrical and magnetic properties on the ME response. The effect of size and configuration has been evaluated in Vitrovac/poly (vinylidene fluoride)(PVDF) and Vitrovac/lead zirconate titanate (PZT) laminated composites. It has been established that the elastic properties and amorphous constitution of PVDF are key parameters governing its ME response, increasing its influence with increasing number of layers in the composite. Good agreement is established when comparing trends reported experimentally in the literature, presenting a curve that rapidly increases their αunit with increasing thickness ratio up to n = 0.3, when saturation is reached. Further, an optimal configuration for PZT multilayers is found, with external magnetostrictive phases and thickness ratio above 0.2, leading to a ME response of 86.7 V/cm. Finally, it has been established that PVDF configurations with external magnetostrictive phases (M-M configuration) show more stable behaviour (without the observation of random peaks) and trends over different number of layers, of about 11.5 V/cm, while P–P configurations present regions with random peaks, that is out of the expected trend and with a ME response (48 V/cm) that closer to the one obtained on ceramic multilayers.